Fabrication of Reusable Ceramic Film Based on Nanostructured Ag/Ag-TiO2 Materials for Photo Catalysis Applications - Awada, Chawki; Shaalan, Nagih M.; Suliman, Noura Al; Alshoaibi, Adil (Challenges and Advances in Chemical Science Vol. 7, 2021)
The objective of this study is to fabricate reusable nanostructured materials based on Ag/TiO2 at low cost for photocatalysis applications. Vertical Agx/TiO2 nanorods were successfully grown by a simple oxidation method of a Ti-Ag coating. The samples were grown in the phase of ceramic-like materials, which can be reusable for many cycles for photocatalysis applications. These ceramic-like Agx/TiO2 nanostructures were prepared by the spin-coating of silver nitrate onto Ti sheets. The presence of silver on the surface of the Ti sheet during the oxidation process helped in the growth of one-dimensional nanostructures. The physical properties of the fabricated ceramic-like nanostructures were studied by varying the concentration of silver on the Ti-sheet before the oxidation. One-dimensional nanostructures with an average size varying within the range of 200–500 nm were grown. The presence of silver made the nanostructure vertically directed. The nanorods were dense at the low and medium concentrations of 5, 10, and 20 mM of silver in contrary to high silver concentrations, where the nanorods were very sparse at 40 mM. Structural analysis showed the anatase and rutile structure of pure TiO2 with distinguishing diffraction lines A(101) and R(110); however, Agx/TiO2 showed a dominant orientation of A(101), confirming the 1D growth. Raman spectra confirmed the presence of TiO2 via the observation of its corresponding phonon modes. The photocatalysis properties of the fabricated ceramic-like nanostructures were performed on methylene blue (MB) as a known target dye. The low- and medium-silver-concentration samples showed a high photocatalytic activity compared to the pure and high-silver-concentration samples.